Study on ionic interaction in carboxymethyl cellulose-kappa carrageenan doped NH4Cl for bio-electrolyte membranes - Leong, Pei Mun (2016)
Energy storage devices that cause disposable and harmful issues make them attracts global concerns due to toxic and hazard materials used as an electrolyte system. Due to this problem, researches are more interested in producing electrolyte based on polymer especially natural resources such as starch, chitosan, pectin, natural rubber, carrageenan derivatives and cellulose derivatives. The main interest in developing polymer as an electrolyte lies in the hope that such system will avoid many of problems accounted when using the hazard materials. In arrears to the fact given, this present research presented CMC/KC doped NH4Cl as biopolymer electrolyte membranes (BEMs). The CMC/KC BEMs system were successfully prepared by using solution casting method and were characterised by different techniques, which are Fourier Transform Infrared (FTIR) spectroscopy, X-ray Diffractometer (XRD) spectroscopy, and Electrical Impedance Spectroscopy (EIS). Based on FTIR analysis, it showed there is complexation has occurred between CMC/KC and NH4Cl due to the shifting of wavenumber. In addition, it also can be found there is changes of intensity with the introducing of NH4Cl in CMC/KC blend and proved that NH4Cl play a role as dopant in the polymer complexes electrolyte system. XRD analysis revealed that the BEMs system has increased in amorphous phase when NH4Cl were added. The ionic conductivity of CMC/KC BEMs system were found to increase and achieved to maximum value at 1.25x10-4 Scm-1 for sample contain with 20 wt.% NH4Cl at ambient temperature. The ionic conductivity-temperature for CMC/KC BEMs system shown the Arrhenius behaviour where all the samples are thermally activated. Rice and Roth method showed that the ionic conductivity in this present system was governed by ionic mobility and diffusion coefficient of charge carriers. This work implies the possible application of CMC/KC BEMs system can be used as an electrolyte system for electrochemical devices.